2015
DOI: 10.1371/journal.pone.0125636
|View full text |Cite
|
Sign up to set email alerts
|

Emerging, Non-PCV13 Serotypes 11A and 35B of Streptococcus pneumoniae Show High Potential for Biofilm Formation In Vitro

Abstract: BackgroundSince the use of pneumococcal conjugate vaccines PCV7 and PCV13 in children became widespread, invasive pneumococcal disease (IPD) has dramatically decreased. Nevertheless, there has been a rise in incidence of Streptococcus pneumoniae non-vaccine serotypes (NVT) colonising the human nasopharynx. Nasopharyngeal colonisation, an essential step in the development of S. pneumoniae-induced IPD, is associated with biofilm formation. Although the capsule is the main pneumococcal virulence factor, the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 44 publications
4
32
2
Order By: Relevance
“…Using an NE S. pneumoniae strain that produces fairly large amounts of biofilm in vitro (15)(16)(17)(18) and a modified culture medium, the present work examined the influence of initial cell concentrations on pneumococcal and NT H. influenzae survival (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using an NE S. pneumoniae strain that produces fairly large amounts of biofilm in vitro (15)(16)(17)(18) and a modified culture medium, the present work examined the influence of initial cell concentrations on pneumococcal and NT H. influenzae survival (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…S. pneumoniae and NT H. influenzae are nasopharyngeal commensals associated with many common respiratory tract infections. Several known virulence factors produced by these pathogens have been associated with their ability to form biofilms, e.g., the CPS, several surface proteins, the neuraminidases NanA and NanB, and various quorum-sensing systems (15,16,18,29,30). Interestingly, recent experimental evidence has shown that some NE S. pneumoniae strains lack several common surface proteins expressed by encapsulated pneumococci (e.g., the cholinebinding proteins PspA, PspC, and PcpA) but express a specific virulence factor, PspK (an LPxTG binding protein), which has been shown to increase NE S. pneumoniae colonization and virulence during AOM (for a review, see reference 11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epidemiology of pneumococcal disease prior to the introduction of pneumococcal vaccines was dominated by the spread of global disease-causing epidemic clones, both multidrug-resistant (MDR) and antimicrobial susceptible clones [6]. The success of epidemic clones, though not well understood, has been linked to certain capsular types [7,8], carriage of a pilus islet [9] and various virulence factors [10]. Mass vaccination has reduced the occurrence of MDR Pneumococcal Molecular Epidemiology Network (PMEN) clones with serotypes covered by the vaccine.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…Possibly, the high rates of comorbidity (Ͼ50%) among patients with an invasive serotype 35B isolate in our study reflect the pathogenic potential of a normally low-pathogenic strain within susceptible populations. In vitro studies show that serotype 35B is capable of forming substantial amounts of biofilm, similar to 19F and 19A, which may facilitate nasopharyngeal colonization and mucosal disease (35). Pneumococcal virulence factors such as pili have been found among CC558 and CC156 isolates (25,36,37).…”
Section: Fig 4 Eburst Analysis Of Penicillin Mic Distribution and Mulmentioning
confidence: 99%